Non-test evaluation instrument on Islamic religious education subjects in the value of monotheism - ristamala, zulfa telian; mustofa, abdul; Mashuda , Ahmad; akil; aziz, abdul (EduGrows: Education and Learning Review, 2025)
This study aims to examine the application and development of non-test evaluation instruments in Islamic Religious Education (PAI), particularly in assessing the values of tawhid (monotheism). Using a qualitative approach through literature review, this research analyzes relevant scientific literature to understand the effectiveness, forms, and challenges in the implementation of non-test evaluations. The findings reveal that instruments such as observation, reflective journals, self-assessment, and religious portfolios can provide a more comprehensive picture of the internalization of tawhid values compared to written tests. However, the implementation of non-test evaluations still faces challenges such as subjective assessment, time constraints, and lack of teacher training. Therefore, strengthening teacher capacity, developing valid and reliable instruments, and institutional support are necessary for the optimal implementation of non-test evaluation in Islamic Religious Education.